Methods for bio-based derivatization of cellulosic surfaces
Glycoside fatty acid esters are used to enhance cellulose materials' hydrophobicity, addressing moisture and oil resistance issues, improving mechanical strength and environmental sustainability in packaging applications.
Patent Information
- Application Number
- JP2023108327
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-03-07
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2037-08-31
Smart Images

Figure 0007623430000019 
Figure 0007623430000020 
Figure 0007623430000021
Abstract
Description
[Technical field]
[0001] The present invention relates generally to the treatment of cellulosic-containing materials, and more particularly to the treatment of cellulose-containing materials. Using bio-based compositions to bind cellulose-based materials ) to make them more hydrophobic / oleophobic. Such compositions and methods are useful for making paper, cardboard, It is useful for surface modification of cellulosic materials, including paper and packaging products. [Background technology]
[0002] Cellulosic materials are used in industry as bulking agents, absorbents, and It has a wide range of applications as a printing component and as a component of inks. The use of cellulosic materials is preferred over other sources due to their strength and chemical / mechanical resilience. (See, for example, Aulin, incorporated herein by reference. (See Cellulose, 2010, 17:559-574). The materials are completely biodegradable once dispersed in the environment and they are completely non-toxic. Cellulose and its derivatives are widely used in food packaging and It is the material of choice for environmentally friendly solutions in applications such as disposable products.
[0003] Nevertheless, many of the advantages of cellulose are due to its high affinity for water / fat. This is counterbalanced by the hydrophilic / oleophilic nature of the material, which is easily hydrated (e.g., Aulin et al., Langmuir (2009), incorporated herein by reference. (See , 25(13):7675-7685.) This is due to the use of absorbents and tissues, etc. Although this is beneficial in some applications, it is necessary to safely package moisture / fat-containing materials (e.g., food). This is problematic when food, especially cooked foods containing large amounts of water and / or fat, Long-term storage of used food is problematic in cellulose trays, but this is e.g. This is because the tray will first get wet and eventually become useless. Compensating for the poor efficiency of maintaining a sufficient coating on cellulosic surfaces due to porosity To achieve this, multiple coatings may be required, which can increase costs.
[0004] This problem is usually caused by wicking into the gaps between the fibers, grease in the folds, etc. The hydrophilic cellulose underneath, including the prevention of ingress of gas or release of attached material, Certain hydrophobic organic materials / fluorocarbons that physically shield the gel from the water / lipids in the gel. This can be achieved by coating cellulose fibers with silicone. For this purpose, materials such as PVC / PEI / PE are customarily used and processed. The coating is physically applied (i.e., spray coated or extruded) onto the surface to be coated.
[0005] Similar problems are encountered when using films to enclose food products within their containers. The film must meet even more stringent requirements than the container itself. It must be able to withstand mechanical stress. In addition, the film must be thin enough to be peeled off and ideally transparent and lipid resistant. / It is grease-resistant, heat-resistant, and impermeable to gases such as CO2, oxygen, and water vapor. It should be non-toxic, non-toxic and hydrophobic. Plastics, fluorocarbons, and resins are the industry's current solutions.
[0006] Reduced cost of base paper without sacrificing biodegradability and / or recyclability Maintains a coating on the surface of the cell and prevents wicking into the interstices of the fibers Hydrophobic properties, including base paper / film, allowing for reduced adhesion of materials to plastic surfaces and it would be desirable to design compostable, "green" bio-based coatings. Summary of the Invention
[0007] The present disclosure provides a method for increasing hydrophobicity while maintaining the biodegradability / recyclability of the cellulosic components. treating a cellulose-containing material with a composition that provides hydrophobicity and / or oleophobicity, The present invention relates to a method for treating cellulosic materials. The method as disclosed comprises depositing a cellulose-based To provide a sugar fatty acid ester (SFAE) bond and to bond the sugar fatty acid ester The bonding reaction does not require the use of organic supports, bases or separate catalysts for the synthesis of cellulosic fibers. It may be applied to fiber or preformed materials.
[0008] In an embodiment, a composition is disclosed that includes an SFAE-bound cellulosic material, is present in a sufficient concentration to cause the bound cellulosic material to exhibit a water contact angle of 90° or greater. and the water contact angle is achieved in the absence of any secondary hydrophobic material, or the SFAE is , sufficient to impart substantial resistance to breaking forces when the cellulosic material is wet. When present in sufficient concentration, resistance is achieved in the absence of any secondary wet strength additives. In certain embodiments, the sugar fatty acid ester comprises at least one sugar and an 8 to 30 carbon fatty acid ester. and the SFAE is the same material as that having no bound SFAE. The dye is present in a concentration sufficient to render the bound cellulosic material hydrophobic as compared to the dye. In this manner, the SFAE may be releasably or non-releasably attached to the cellulosic material. It bonds like this.
[0009] In a further embodiment, the SFAE is carried out to determine whether the bound cellulosic material has a water contact angle of 90° or greater. The water contact angle is measured in the absence of any secondary hydrophobic material. The SFAE achieves a substantial reduction in the breaking force when the cellulosic material is wet. The wet strength additives are present in a concentration sufficient to impart substantial resistance to the non-ionic surfactants of any secondary wet strength additives. This is achieved in the presence of
[0010] In one embodiment, the SFAE is attached as a coating on the cellulosic material, and the SF The AE is applied to the surface of the cellulosic material at a concentration of at least 0.1 g / m 2 At a coating weight of In another embodiment, the cellulosic material is a solution containing cellulose fibers. In this case, the SFAE must be present at a concentration of at least 0.025% (wt / wt) of the total fibers present. There is.
[0011] In one embodiment, the aliphatic group is derived from a natural source. In a related embodiment, the natural source is , an oilseed, and SFAE is sucrose soybean fatty acid. In some embodiments, an aliphatic group contains fully saturated bonds or a mixture of saturated and unsaturated bonds.
[0012] In another embodiment, the cellulosic material is microfibrillated cellulose (MFC), It further comprises nanofibrillated cellulose, or cellulose nanocrystals.
[0013] In further embodiments, the composition comprises polyvinyl alcohol (PvOH), polylactic acid, a viscosity modifier, May include earth, talc, starch, glyoxyl, prolamin and combinations thereof.
[0014] In one embodiment, the sugar fatty acid ester is mono-, di-, tri-, tetra-, penta-, hexa-, hepta-, octa-esters or mixtures thereof, optionally with The product has a saturated aliphatic group or a combination of saturated and unsaturated fatty acids. The sugar fatty acid ester may comprise one or more sugar fatty acid esters.
[0015] In another embodiment, the composition is biodegradable and / or compostable. In such a manner, cellulose-containing base materials are used in paper, cardboard, paper pulp, food storage cartons, etc. Tons, food storage bags, shipping bags, coffee or tea containers, tea bags, bacon bacon board, diapers, weed control / barrier fabrics or films, Rubbing film, flower pots, filling beads, bubble wrap, oil absorbent materials, laminates, envelopes , gift cards, credit cards, gloves, raincoats, OGR paper, shopping bags, compost bags, Release paper, tableware, containers for holding hot or cold drinks, cups, paper towels bottles for storing carbonated liquids, insulation materials, bottles for storing non-carbonated liquids, food packaging materials Films, garbage disposal containers, food handling equipment, cup lids, fabric fibers, water storage and transportation Equipment, storage and transport equipment for alcoholic or non-alcoholic beverages, external cases for electronic products linings or screens, interior or exterior parts of furniture, curtains, upholstery materials, Rooms, boxes, sheets, trays, pipes, water pipes, pharmaceutical packaging, clothing, medical devices, This includes contraband, camping equipment, molded cellulosic materials, and combinations thereof.
[0016] In one embodiment, the sugar fatty acid ester is an ether, ester, thio, amino, phospho or or a combination thereof.
[0017] In one embodiment, the cellulosic material is tailored for hydrophobic and / or oleophobic resistance. A method for configurably derivatizing a cellulosic material comprising contacting the cellulosic material with a sugar fatty acid ester. and treating the contacted cellulosic material with heat, radiation, a catalyst, or a combination thereof. In addition, the process is performed for a period of time sufficient to allow the sugar fatty acid esters to bind to the cellulosic material. In a related aspect, the method further comprises: The method may include removing the tell.
[0018] In one embodiment, the method includes adding polyvinyl alcohol (PvOH). The PvOH and / or sugar fatty acid ester may be used separately or in combination. , optionally added as an emulsion.
[0019] In another embodiment, the cellulosic material is microfibrillated cellulose (MFC), Includes nanofibrillated cellulose, or cellulose nanocrystals.
[0020] In one embodiment, the resulting solid cellulose-containing material is used in the manufacture of paper, cardboard, paper pulp, food Storage cartons, compost bags, food storage bags, release paper, shipping bags, shopping bags, weed protection / barrier Fabric or film, mulching film, flower pot, filling beads, bubble wrap, oil absorbent Materials, Laminates, Envelopes, Gift Cards, Credit Cards, Gloves, Raincoats, OG R paper, tea bags, coffee or tea containers, bacon paper, insulating materials, lids, food Vessels, containers for holding hot or cold drinks, cups, dishes, containers for storing carbonated liquids bottles for storing non-carbonated liquids, food packaging films, garbage disposal containers, food handling Equipment, fabric fibres, water storage and transport equipment, storage and transport equipment for alcoholic or non-alcoholic beverages and transport equipment, outer casings or screens for electronic products, interior or exterior parts of furniture products, curtains, interior decoration materials, fabrics, films, boxes, sheets, trays, pipes, water pipes, Clothing, medical devices, contraceptives, camping equipment, pharmaceutical packaging, insulating materials, molded ceramics In a related aspect, the present invention relates to products that include cellulose materials, as well as combinations thereof. Thus, the resulting product is biodegradable and / or compostable.
[0021] In an embodiment, microfibrillated cellulose (MFC)-containing pulp or MFC A cellulosic material comprising a coating and a sugar fatty acid ester is disclosed. In this way, the materials are polyvinyl alcohol (PvOH), polylactic acid (PLA), clay, May contain compounds including talc, glyoxyl, prolamin and combinations thereof. .
[0022] In one embodiment, the material is paper or film. In a related embodiment, the material is In a further related aspect, the material is hydrophobic and oleophobic. The materials represent 3M Grease KIT test values between 3 and 12.
[0023] In an embodiment, the sugar fatty acid ester is mixed with water, a buffer, polyvinyl alcohol, carbohydrate, and the like. CMC, milk protein, wheat gluten, gelatin, prolamin , soy protein isolate, starch, acetylated polysaccharides, alginate, carrageenan , chitosan, inulin, long chain fatty acids, wax, agar, alginate, glycerol, galactose , lecithin, poloxamer, mono-, di-glycerol, monosodium phosphate, monosodium tearates, propylene glycol, detergents, cetyl alcohol, and combinations thereof and a second component comprising the sugar fatty acid ester. It contains at least one sugar and at least one aliphatic group containing from 8 to 30 carbons.
[0024] In one embodiment, the sugar ester is mono-, di-, tri-, tetra-, penta-, hexa- The ester may be a -, hepta-, octa-ester or a mixture thereof.
[0025] In a related embodiment, the emulsion and the agarite, ester, diester, ether aldehydes, ketones, amides, nitriles, aromatics (e.g., xylene, toluene), acid halides , anhydrides, talc, alkyl ketene dimer (AKD), alabaster, alganic acid (alg anic acid), alum, albarine, adhesive, carbonated Sodium, barium sulfate, chlorine dioxide, clay, dolomite, diethylenetriaminepentaacetic acid, EDTA, enzymes, formamidine sulfate, guar gum, gypsum, lime, magnesium bisulfate, Milk of lime, milk of magnesia, polyvinyl alcohol (PvOH) ), rosin, rosin soap, satin, soap / fatty acid, sodium bisulfate, soda ash, titani A, surfactants, starch, modified starch, hydrocarbon resins, polymers, waxes, SFA A carrier composition containing a drug, including E, polysaccharides, proteins, and combinations thereof is disclosed. In further related embodiments, the agent has formula (II) or (III): R-CO-X Formula (II) X-CO-R-CO-X1 Formula (III) (wherein R is a straight chain, branched chain, or cyclic aliphatic hydrocarbon having from 6 to 50 carbon atoms. X and X1 are independently Cl, Br, R-CO-OR, or O(C In a related embodiment, the alkanoic acid is an alkanoic acid derivative having an alkanoic acid group having a carboxyl group and a carboxyl group. When the derivative has formula (III), X or X1 are the same or different.
[0026] In an embodiment, a fluffy material is disclosed that includes a sugar fatty acid ester and cellulose pulp. will be done.
[0027] In an embodiment, a method of making a fluffy material includes the steps of: The steps of mixing pulp and water, stirring until homogeneous, and extracting the mixture. and drying the fiber mat with applied heat. and b) applying a pressure to the fibers to form a crosslinked fiber. This may also be the case.
[0028] In an embodiment, the method of producing a sugar fatty acid ester coated cellulosic material comprises: The polymer comprises a sugar fatty acid ester (SFAE), polyvinyl alcohol, and optionally a crosslinked polymer. The fatty acid may be saturated or may be a mixture of saturated and unsaturated fatty acids. The method includes the steps of combining fatty acids, heating the mixture, and subjecting the heated mixture to a solidification process. and a step of coating the resulting cellulosic material on the surface thereof. In a related aspect, the coating material is hydrophobic. The material is hydrophobic and / or oleophobic.
[0029] In one embodiment, the SFAE is a mono-, di-, tri-, tetra-, penta-, hexa-, hepta-, octa-substituted ester. In a related embodiment, the sugar is raffinose, maltodextrose, galactose, sucrose, Combinations containing glycerol, glucose, fructose, and maltose. combinations containing lactose and mannose, combinations containing erythrose, isomaltose , isomaltulose, trehalose, trehalulose, cellobiose, laminaribiose , chitobiose, and combinations thereof. , the disaccharide is sucrose.
[0030] In one embodiment, the cross-linking agent is a dialdehyde. In a further related embodiment, the compound produced by the above method is A cellulosic material is disclosed.
[0031] In an embodiment, a size vector comprising a sugar fatty acid ester, PvOH, and optionally a cross-linking agent. In a related aspect, the sugar fatty acid ester is a sucrose fatty acid ester. In a further related embodiment, the crosslinker is a dialdehyde. The aldehyde is glyoxal. [Brief description of the drawings]
[0032] [Figure 1]1 is a scanning electron micrograph (SEM) of untreated, hollow Whatman filter paper (magnification 58x). [Diagram 2] SEM of untreated porosity Whatman filter paper (magnification 1070x). [Diagram 3] FIG. 2 shows a side-by-side SEM comparison of paper made from recycled pulp before (left) and after (right) coating with microfibrillated cellulose (MFC) (27x magnification). [Figure 4] FIG. 1 shows a side-by-side SEM comparison of paper made from recycled pulp before (left) and after (right) coating with MFC (98x magnification). [Diagram 5] FIG. 1 is a graph showing water permeability in papers treated with various coating formulations: polyvinyl alcohol (PvOH) (diamonds), 1:1 (v / v) SEFOSE®+PvOH (squares), Ethylex (starch) (triangles), and 3:1 (v / v) SEFOSE®+PvOH (crosses). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] Before describing the compositions, methods and methodologies of the present invention, the present invention is not limited to the specific compositions described. The compositions, methods and experimental conditions are not limited, and therefore the compositions, methods and conditions may vary. It should be understood that the scope of the present invention is limited only by the appended claims. To be limited, the terminology used herein is intended to describe specific embodiments. It should also be understood that these are for illustrative purposes only and are not intended to be limiting.
[0034] As used in this specification and the appended claims, a different definition is clearly given where the context requires. Unless otherwise indicated, the singular forms "a," "an," and "the" include plural referents. Thus, for example, "a saccharide fatty acid ester" A reference to "sugar fatty acid ester" refers to one or more sugar fatty acid esters, and / or or compositions of the type described herein that will become apparent to those of skill in the art upon reading this disclosure.
[0035] Unless otherwise defined, all technical and scientific terms used herein are and have the same meaning as commonly understood by a person skilled in the art to which the present invention pertains. It is understood that modifications and variations are encompassed within the spirit and scope of the disclosure. Any methods and materials similar or equivalent to those described herein can be used in the practice or otherwise of the present invention. may be used in the test.
[0036] As used herein, the terms "about" and "approximately" are used interchangeably. "Substantially," "significantly," and "significantly" "notably" will be understood by those of skill in the art and will vary depending on the context in which they are used. The term may vary to some extent in its use if its use is not clear to a person of ordinary skill in the art given the context in which it is used. When present, "about" and "approximately" mean plus or minus 10% of a particular item. "Substantially" and "significantly" mean plus or minus 10% of a particular item. "Comprising" and "consisting essentially of" mean more than "consisting essentially of" refers to the practice in the art. It has a similar meaning.
[0037] In an embodiment, the present disclosure provides a method for treating the surface of cellulose fibers with a sugar fatty acid ester. The resulting surface has cellulosic hydroxyl groups shielded by bulky organic chains. These sugar fatty acid esters are particularly strongly hydrophobic because As such, they are easily digested when removed, for example, by bacterial enzymes. The surface is extremely heat resistant and can withstand temperatures as high as 250°C. The material can be more impermeable to gases than the underlying base substrate. In any embodiment in which a cellulose material may be used, the hydrophilic surface of the cellulose may be derivatized. It is an ideal solution to the problem of data erosion.
[0038] An advantage of the products and methods as disclosed herein is that the coating composition Made from recyclable agricultural resources, i.e. sugars and vegetable oils; biodegradable has a low toxicity profile making it suitable for food contact; has a high level of water resistance Even the surface friction coefficient of the paper / cardboard surface can be adjusted to reduce (i.e. (does not make the paper too slippery for downstream processing or end use); special emulsifying equipment or and that it may or may not be used in conjunction with an emulsifier or emulsifier; Compatibility with cycle programs, i.e. polyethylene, polylactic acid or wax This includes not adversely affecting recycling operations, as does coating paper. .
[0039] As used herein, "biobased" means any material that is made from living (or "Materials manufactured from living organisms" means materials intentionally produced from substances obtained from living organisms (currently living or formerly living organisms). In a related embodiment, the material containing at least about 50% of such substances is biocompatible. is considered the base.
[0040] As used herein, the term "bind," including its grammatical variations, is intended to mean "Agglomerate" means to aggregate or cause to aggregate as a single mass essentially.
[0041] As used herein, “cellulosic” refers to a material (e.g., , bags, sheets) or natural materials that can be molded or extruded as films or filaments. , synthetic or semi-synthetic materials, which are such objects or films or fillers It can be used to make cellulose membranes, i.e., structures and functions similar to cellulose. These include coatings and adhesives (e.g., carboxymethylcellulose). In another example, glyceryl esters, which form the major components of cell walls in most plants, may be used. Complex carbohydrates made up of glucose units (C6H 10 O5) n Cellulose, which is It is cellulose-based.
[0042] As used herein, "coating weight" refers to the weight of material ( The weight of the material (wet or dry) is expressed in units of the specified unit weight or unit weight in grams per square meter. It is expressed in pounds per kilogram.
[0043] As used herein, "compostable" refers to these solids. This means that the product is biodegradable in soil.
[0044] As used herein, "edge wicking" refers to These include, but are not limited to, capillary penetration into the pores between the fibers, diffusion through the fibers and bonds, and at the outer boundary of the paper structure by one or more mechanisms including surface diffusion on the fibers. It refers to the sorption of water into the paper structure. In a related aspect, the glycosphingolipids as described herein The fatty acid ester-containing coating prevents edge wicking on the treated product. In one embodiment, the same is true for grease / oil that gets into creases that may be present in paper or paper products. Such a "grease creasing effect" exists. " refers to the collection of grease within a paper structure formed by folding, compressing or squeezing the paper structure. It can be defined as
[0045] As used herein, "effect," including its grammatical variations, refers to a particular material. This means that the material has certain characteristics.
[0046] As used herein, "hydrophobic material" means a material that does not attract water. For example, wax, rosin, resin, sugar fatty acid ester, diketene, shellac, acetic acid Vinyl, PLA, PEI, oils, fats, lipids, other water repellent chemicals, or combinations thereof is a hydrophobic material.
[0047] As used herein, "hydrophobic" refers to a tendency to repel and not absorb water. It means the property of having a direction.
[0048] As used herein, "lipid resistance" or "lipophobicity" refers to Lipophobicity is the tendency to repel and not absorb lipids, grease, and fats. In a related embodiment, grease resistance is measured using the "3M KIT" test. Or it can be measured by TAPPI T559 Kit test.
[0049] As used herein, "cellulose-containing material" or "cellulosic material" refers to " refers to a composition consisting essentially of cellulose. For example, such a material may be Including, but not limited to, paper, paper sheets, cardboard, paper pulp, food storage cartons, paper Chimento paper, cake board, butcher paper, release paper / liner, food storage Bags, shopping bags, shipping bags, cardboard for bacon, insulation, tea bags, coffee or tea containers, compost bags, dishes, containers for holding hot or cold drinks, cups, lids, Plates, carbonated liquid storage bottles, gift cards, non-carbonated liquid storage bottles, food packaging Film, garbage disposals, food handling equipment, textile fibres (e.g. cotton or cotton blends), water Storage and transport equipment, alcoholic or non-alcoholic beverages, outer casings for electronic products or may include screens, interior or exterior pieces of furniture, curtains and upholstery materials. .
[0050] As used herein, "release paper" refers to a paper that has a sticky surface. A sheet of paper used to prevent premature adhesion to adhesives or mastics. In one aspect, the coating as disclosed herein has a low surface energy Replaces the use of silicone or other coatings to create materials with high energy The determination of surface energy can be used to increase or decrease the surface energy by measuring the contact angle. and (e.g., optical tensiometers and / or high pressure chambers; Dyne Testi ng, Staffordshire, UK), or a surface energy test pen or By using inks (e.g., Dyne Testing, Stafford shire, UK) can be easily achieved.
[0051] As used herein, "peelability" with respect to SFAE refers to the ability of the SFAE coating to Once applied, the coating is removable from the cellulosic material (e.g., by changing the physical properties). As used herein, the term "removable" means "able to be removed by manipulating the In this case, "non-peeling" with respect to SFAE means that the SFAE coating, once applied, substantially irreversibly bound to cellulose-based materials (e.g., removable by chemical means) This means that
[0052] As used herein, "fluffy" refers to raw cotton or stylophoric It means a light solid material having the appearance of a fluffy peanut. In an embodiment, the fluffy material is , nanocellulose fibers (e.g., MFC), cellulose nanocrystals, and / or cellulose The resulting fibers or filaments may be made from filaments and sugar fatty acid esters. The crystalline or hydrophobic nature of the solubility of the solubility in composites (e.g. concrete, plastics) It can be used in the preparation of various kinds of adhesives, such as sticks.
[0053] As used herein, "fibers in solution" or "Pulp" is a material made by chemically or mechanically extracting cellulose fibers from wood, fiber crops, or waste paper. In a related aspect, the term "lignocellulosic fibrous material" refers to a lignocellulosic fibrous material prepared by isolating In the case where the cellulose fibers are treated by the method as disclosed herein, The cellulose fibers themselves contain bound sugar fatty acid esters as isolated entities, and the bound Cellulosic fibers have separate and distinct properties from free fibers (e.g., pulp- or Cellulose fiber - or nanocellulose or microfibrillated cellulose - glycolipid Fatty ester bonded materials do not form hydrogen bonds between fibers as readily as non-bonded fibers.
[0054] As used herein, "repulpable" refers to a paper or cardboard product that is , breaking it down into soft, shapeless chunks for reuse in paper or cardboard production. This means that the material is suitable for use in a wide range of applications.
[0055] As used herein, "tunable" includes its grammatical variations. means adjusting or adapting a process to achieve a particular result. .
[0056] As used herein, "water contact angle" means the angle measured through a liquid. The liquid / gas interface is in contact with a solid surface. This defines the wettability of a solid surface by a liquid. The contact angle is a quantification of how strongly the liquid and solid molecules each adhere to themselves. How strongly liquid and solid molecules interact with each other compared to how strongly liquid and solid molecules interact with each other On many highly hydrophilic surfaces, a drop of water will form at an angle of 0° to 30°. Antennae are shown. Generally, a solid surface is considered hydrophobic if the water contact angle is greater than 90° Water contact angles can be readily obtained using an optical tensiometer (e.g., Dyne Te sting, Staffordshire, UK).
[0057] As used herein, "water vapor permeable" refers to the ability to breathe or transport moisture. It refers to the ability of a fabric to withstand heat. There are at least two different methods of measurement. The first is ISO1 MVTR Test (Water Vapor Transmission Rate) according to 5496, which measures the water vapor transmission rate (WV P), and therefore describes the degree of transpiration transfer to the outside air. The measurement is how many grams per 24 hours. of moisture (water vapor) passes through one square meter of fabric (the higher the level, the Highly breathable).
[0058] In one embodiment, the TAPPI T 530 Hercules size test (i.e., Waterfastness can be determined using the Ink Resistance Paper Sizing Test. Ink resistance by the s method is best classified as a direct measurement of penetration. Another classification is the penetration rate test. There is no single best test. The choice of test depends on the end use and mill control needs. This method is a mill controlled sizing test to accurately detect changes in sizing levels. It is particularly suitable for use as a marker for the ink float test. while providing reproducible results, shorter test times, and automated endpoint determination. provide.
[0059] Sizing, as measured by the resistance of aqueous liquids to penetration or absorption into the paper, is an important property of many papers, such as bags, corrugated cardboard, meat wrap, writing paper, etc. , and some printing grades.
[0060] This method is applicable where an acceptable correlation has been established between the test values and the end-use performance of the paper. In some cases, it may be used to monitor paper or cardboard production for a particular end use. Due to the nature of the test and the penetrant, this will not be applicable to all end use requirements. This method measures sizing by penetration rate. The method measures sizing by surface contact, surface penetration, or absorption. , are selected based on their ability to mimic the means of water contact or absorption in the end use application. The method can also be used to optimize the cost of sizing chemical usage.
[0061] As used herein, "oxygen permeability" refers to the ability of a polymer to pass gases or fluids. The oxygen permeability (Dk) of a material is determined by the diffusion coefficient (D) (i.e., The rate at which oxygen molecules move across a material and the solubility (k) (or the amount of oxygen absorbed in a material per volume) The oxygen permeability (Dk) is a function of the amount of oxygen molecules absorbed. The oxygen permeability (Dk) value is typically between 10 and 15 0×10 -11 (cm 2 ml O2) / (s ml mmHg). A semi-logarithmic relationship was shown between the hydrogel water content and oxygen permeability (unit: Barrer). The International Organization for Standardization (ISO) has established the SI unit hectopascal (hPa) for pressure. is used to specify the transparency. Therefore, Dk=10 -11 (cm 2 ml O2 ) / (s ml hPa). The barrer unit is obtained by multiplying it by the constant 0.75. This can be converted to hPa using the following formula:
[0062] As used herein, "biodegradable," including its grammatical variations, refers to the ability of a living organism to degrade or decompose. This means that it can be broken down by (for example by microorganisms) into particularly harmless products.
[0063] As used herein, "recyclable," including its grammatical variations, refers to a material that is can be processed to make them suitable for reuse, or (used and / or discarded means said material that can be processed (together with
[0064] As used herein, "Gurley seconds" or "Gurley number" means 100 cubic centimeters (deciliters) of air will move 1.0 square inch of a given material through 4 A simple formula that describes the number of seconds required to pass a pressure difference of .88 inches of water (0.176 psi) (ISO5636-5:2003) (porosity). The "rley number" is the force (in millimeters) required to bend a material held vertically a given amount. Gram-force is a unit of force measured for a piece of the material. The equipment was from Swift Precision Instruments (Troy, New York). rk) can be measured.
[0065] The HLB, or hydrophilic-lipophilic balance, of a surfactant is either hydrophilic or lipophilic. It is a measure of degree and is determined by calculating values for different regions of the molecule.
[0066] The Griffin method for nonionic surfactants, described in 1954, is as follows: It is. HLB=20*M h / M In the formula, M h is the molecular weight of the hydrophilic portion of the molecule, M is the molecular weight of the entire molecule, and is between 0 and The results are presented on a scale of 1 to 20. An HLB value of 0 corresponds to a completely lipophilic / hydrophobic molecule. Correspondingly, a value of 20 corresponds to a completely hydrophilic / oleophobic molecule.
[0067] The HLB value can be used to predict the surfactant properties of a molecule. <10: Fat-soluble (water-insoluble) >10: Water soluble (lipid insoluble) 1.5~3: Defoamer 3-6: W / O (water-in-oil) emulsifiers 7-9: Wetting and spreading agents 13~15: Detergent 12-16: O / W (oil-in-water) emulsifier 15-18: Solubilizers or hydrotropes
[0068] In some embodiments, the sugar fatty acid esters ( Or the composition containing the ester) may have an HLB value in a lower range. In embodiments, the sugar fatty acid ester (or the ester) as disclosed herein is The HLB value of the composition (including the ester) may be in the medium to higher range.
[0069] As used herein, "SEFOSE®" refers to one or more unsaturated or multiple fatty acids, Procter & Gamble Chemicals (C It is commercially available from Incinnati, Ohio under the trade name SEFOSE 1618U. Refers to sucrose fatty acid esters (soybean oil fatty acid esters) made from soybean oil. (See polysucrose soyate below). As used herein, " OLEAN® is a compound of the formula C n+12 H 2n+22 O 13 With Procte Refers to sucrose fatty acid esters available from R&Gamble Chemicals. , all fatty acids are saturated.
[0070] As used herein, "soybean oil fatty acid esters" refers to fatty acid esters of soybeans. It means a mixture of salts of fatty acids from oils.
[0071] As used herein, "oilseed fatty acids" refers to Including but not limited to soybeans, peanuts, rapeseed, barley, canola, sesame seeds, cottonseed, palm kernel, grape seed, olive, safflower, sunflower, copra, corn, Coconut, flaxseed, hazelnut, wheat, rice, potato, cassava, beans, cabbage By this is meant fatty acids from plants including melina seed, mustard seed, and combinations thereof.
[0072] As used herein, "wet strength" refers to the strength with which paper can be made when wet. It is a measure of how well the web of fibers that holds the paper together can resist breaking forces. Wet strength was measured using the Thwing-Albert Instrument Compa Measured using the Finch wet strength device from West Berlin, NJ Here, wet strength is typically achieved using a sponge, cationic glyoxylated resin, , polyamidoamine-epichlorohydrin resin, polyamine-epichlorohydrin resin, This can be achieved, for example, by wet strength additives such as epoxide resins. The SFAE coated cellulosic material as disclosed in the document is free of such additives. Such wet strength is achieved in the absence of agents.
[0073] As used herein, "wet" means covered or saturated with water or another liquid. This means that
[0074] In an embodiment, the process as disclosed herein comprises the step of: or by binding to a cellulosic surface. The emulsion containing the sugar fatty ester is then contacted with the emulsion as a carrier for the coating agent. the process comprises dissolving the cellulosic material in a sugar fatty acid ester, emulsion, or both, and subjecting the contacted cellulosic material to heat, radiation, a catalyst or or a combination thereof, a sugar fatty acid ester or a coating agent is bound to the cellulosic material. In a related embodiment, such radiation is used to expose the nucleus to a sufficient amount of light to cause it to combine. may include, but is not limited to, UV, IR, visible light, or a combination thereof. In another related embodiment, the reaction is carried out at room temperature (i.e., 25° C.) to about 150° C., about 50° C. to about 100°C, or from about 60°C to about 80°C.
[0075] Additionally, the binding reaction between the SFAE and the cellulosic material produces a substantially pure sugar-fatty acid ester. Alternatively, the sugar fatty acid ester may be part of an emulsion. In one embodiment, the sugar fatty acid ester emulsion may be a mono-, di-, tri- Contains mixtures of tri-, tetra-, penta-, hexa-, hepta-, or octaesters In another embodiment, the emulsion may contain, but is not limited to, milk proteins. protein (e.g., casein, whey protein, etc.), wheat gluten, gelatin, prolamins ( (e.g. corn zein), soy protein isolate, starch, modified starch, acetonitrile, Chilled polysaccharides, alginate, carrageenan, chitosan, inulin, long chain fatty acids, wax , and combinations thereof.
[0076] In an embodiment, the sugar fatty acid ester or emulsion comprises an epoxy group of said ester. Derivatives (see, for example, U.S. Pat. No. 6,393,363, which is incorporated herein by reference) Such epoxy derivatives may be mixed with, for example, For example, it can function as an adhesive.
[0077] In an embodiment, the cellulosic material is polyvinyl alcohol (PvOH) and / or Alternatively, the addition of prolamins can render the lipophobic. In one embodiment, the prolamins are These include glycine, gliadin, hordein, secalin, katirin and avenin. In a related embodiment, the prolamine is zein.
[0078] In embodiments, a catalyst and an organic support (e.g., a volatile organic solvent) are used to carry out the binding reaction. No additional chemical compounds are required, for example, and no accumulation of materials is contemplated using the methods as disclosed. In a related embodiment, the reaction time is substantially instantaneous (i.e., less than 1 second). Furthermore, the resulting materials exhibit low blocking.
[0079] As disclosed herein, fatty acid esters of all sugars, including monosaccharides, disaccharides, and trisaccharides, are Stell is adaptable for use in connection with this aspect of the invention. Sugar fatty acid esters are mono-, di-, tri-, tetra-, penta-, hexa-, hepta- or octaesters, and combinations thereof, e.g., the fatty acid moiety may be , saturated, unsaturated or a combination thereof.
[0080] Without being bound by theory, the interaction between the sugar fatty acid ester and the cellulosic material may be hydrophobic, van der Waals interactions, or covalent bonds, or combinations thereof In a related aspect, sugar fatty acid esters are attached to cellulosic materials. is substantially irreversible (e.g., SFAEs containing a combination of saturated and unsaturated fatty acids using.
[0081] Furthermore, at sufficient concentrations, the binding of sugar fatty acid esters alone can also be used to bind cellulosic materials. Sufficient to render it hydrophobic, i.e., hydrophobic, is a wax, rosin, resin, diketene , shellac, vinyl acetate, PLA, PEI, oil, other water repellent chemicals or combinations thereof This is accomplished in the absence of the addition of a secondary hydrophobic material, e.g., Other properties of cellulose-based materials, such as strengthening, stiffening, and bulking, are not possible due to the sugar fatty acid ester bond alone. This is achieved by:
[0082] The advantage of the invention as disclosed is that multiple fatty acid chains are present in the cellulose and in the two structures. For example, the disclosed sucrose fatty acid esters are reactive with sugar molecules. The polymer creates a rigid crosslinked network that is ideal for use in paper, cardboard, airlaid and wet-laid nonwovens. and strength improvements in fibrous webs such as fabrics. This is typically Not found in sizing or hydrophobic treatment chemistries. Such sugar fatty acid esters also exhibit moisture resistance, a property not found using many other water-resistant chemistries. Generates / increases moisturizing strength.
[0083] Another advantage is that the sugar fatty acid esters as disclosed soften the fibers and fill the spaces between them. The goal is to increase the mass and thus increase the bulk without substantially increasing the weight. Additionally, the fibers and cellulosic materials modified as disclosed herein have the following properties: In addition, for example, water can penetrate into the sheet by overcoming a low surface energy barrier. It cannot be easily "pushed" into
[0084] Saturated SFAEs are typically solids at normal processing temperatures, whereas unsaturated SFAs E is typically a liquid. This allows other coating components, which are typically hydrophilic, to be Uniform distribution of saturated SFAE in water-based coatings without significant interaction or incompatibility with This allows the formation of a stable dispersion. without adversely affecting coating performance characteristics, uniform coating application, or coating This allows for the preparation of a highly concentrated saturated SFAE. After the coating layer is heated, dried and solidified, the particles of saturated SFAE melt and spread, becoming hydrophobic. In embodiments, the composition produces a bulky fibrous structure that retains its strength even when exposed to water. Generally, a fibrous slurry, which is a dense structure in a dry form, is dissolved in water. The molded fiber products made using the methods disclosed herein are readily degraded after exposure to is lightweight, strong, and resistant to exposure to water and other liquids; paper plates, beverage containers (e.g. For example, cups, lids, food trays and packaging.
[0085] In an embodiment, the sugar fatty acid ester is mixed with polyvinyl alcohol (PvOH). As disclosed herein, In the past, a synergistic relationship between sugar fatty acid esters and PvOH has been demonstrated. PvOH is a good film former by itself and forms strong hydrogen bonds with cellulose. However, it is not very resistant to water, especially hot water. In this case, the use of PvOH helps to emulsify the sugar fatty acid ester into the aqueous coating. In an embodiment, PvOH is a polysaccharide having a high concentration of OH groups for crosslinking sugar fatty acid esters along the fiber. This provides a rich source of phosphate binder which increases the strength of the paper, especially in wet conditions, beyond that possible with PvOH alone. Increases the strength and water resistance of the saturated sugar fatty acid ester with a free hydroxyl on the sugar. In the case of ter, cross-linking agents such as dialdehydes (e.g., glyoxal, glutaraldehyde, etc.) may also be used.
[0086] In an embodiment, the sugar fatty acid ester comprises a sucrose ester of a fatty acid, or To make or otherwise provide the sugar fatty acid esters of the present invention, Many methods for this purpose are known and available, and all such methods are within the scope of the present invention. It is believed that the present invention is available for a wide range of uses. For example, in certain embodiments, These include, but are not limited to, soybean oil, sunflower oil, olive oil, canola oil, peanut oil, One or more fatty acid moieties obtained from oilseeds, including corn oil, corn oil, and mixtures thereof. It may be preferred that the fatty acid esters are synthesised by esterifying sugars with
[0087] In embodiments, the sugar fatty acid ester may include, but is not limited to, a sucrose moiety. The sugar moiety may be substituted at one or more of its hydroxyl hydrogens by an ester moiety. In a related embodiment, the disaccharide ester has the structure of Formula I: [ka] wherein "A" is hydrogen or has the following structure I: [ka] In the formula, "R" is a linear, branched, or cyclic, saturated or unsaturated alkyl group having from about 8 to about 40 carbon atoms. or unsaturated aliphatic or aromatic moiety, with at least one "A" If yes, at least two, at least three, at least four, at least five, at least At least six, at least seven, and all eight "A" moieties conform to Structure I. In embodiments, the sugar fatty acid esters as described herein can be mono-, di-, tri-, tetra ... Tri-, penta-, hexa-, hepta-, or octa-esters, and combinations thereof The aliphatic groups may be all saturated or may be saturated and / or may contain unsaturated groups or combinations thereof.
[0088] Suitable "R" groups are one or more substituents that may occur on any carbon in the moiety. The term "aliphatic moiety" includes any form of aliphatic moiety, including those containing Aliphatic moieties containing functional groups such as ether, ester, thio, amino, phospho, etc. are also included. , oligomeric and polymeric aliphatic moieties, such as sorbitan, polysorbitan and poly Contains an alcohol moiety. Can be added to an aliphatic (or aromatic) moiety that contains an "R" group Examples of functional groups include, but are not limited to, halogen, alkoxy, hydroxy, amino, In one embodiment, the moiety has a crosslinking functionality. In another embodiment, the SFAE may be crosslinked to the surface (e.g., activated clay / pigment particles). In another embodiment, the double bonds present on the SFAE may be reacted with other surfaces. can be used to promote
[0089] Preferred disaccharides are raffinose, maltodextrose, galactose, sucrose, glucose, glucose combination, fructose combination, maltose, lactose, mannose combination A combination of erythrose, isomaltulose, trehalose, and trehalose. including cellulose, cellobiose, laminaribiose, chitobiose, and combinations thereof. .
[0090] In an embodiment, the substrate for the addition of fatty acids is starch, hemicellulose, lignocellulose, or the like. The composition may include, for example, cephalosporins ...
[0091] In an embodiment, the composition comprises a starch fatty acid ester, the starch being Dentco Corn starch, waxy corn starch, potato starch, wheat starch, corn starch Starch, sago starch, tapioca starch, sorghum starch, sweet potato starch, The compounds may be obtained from any suitable source, including but not limited to, sodium phosphate esters, sodium phosphate diphosphate esters, and mixtures thereof.
[0092] More specifically, the starch may be unmodified starch or may be modified by chemical, physical or other methods. Alternatively, it may be a starch modified by enzyme modification.
[0093] Chemical modification involves the modification of starch with chemicals resulting in modified starch (e.g., plastarch materials). Chemical modifications include, but are not limited to, depolymerization of starch, Starch oxidation, starch reduction, starch etherification, starch esterification, starch These include starch nitrification, starch degreasing, starch hydrophobization, etc. Chemically modified starch is also Chemically modified starch can be prepared by using any combination of chemical treatments. Examples of such compounds include alkenyl succinic anhydrides, especially o-, o-, and o-, to produce hydrophobically esterified starches. Reaction of ctenylsuccinic anhydride with starch; 2, to produce cationic starch Reaction of 3-epoxypropyltrimethylammonium chloride with starch; Hydroxy Reaction of ethylene oxide with starch to produce ethyl starch; Reaction of hypochlorite with starch to produce acid depolymerized starch; with starch; methanol, ethanol, propane to produce defatted starch This includes the degreasing of starch with solvents such as methanol, methylene chloride, chloroform, and carbon tetrachloride.
[0094] The physically modified starch is physically treated in any manner to provide the physically modified starch. Physical modifications include, but are not limited to, starch modified by dehydration in the presence of water. Heat treatment of starch, heat treatment of starch in the absence of water, heat treatment of starch by any mechanical means These include crushing the starch granules, and pressurizing the starch to melt the starch granules. Pudding can also be prepared by using any combination of physical treatments. Examples of modified starches include those that can be oxidized in an aqueous environment to swell the starch granules without rupturing them. Heat treatment of starch; Heat treatment of anhydrous starch granules to effect polymer rearrangement; Mechanical disintegration and delaminating the starch granules using an extruder to effect melting of the starch granules. This involves pressure treatment of starch granules.
[0095] The enzyme-modified starch may be enzymatically treated in any manner to provide the enzyme-modified starch. Enzymatic modifications include, but are not limited to, alpha amylase, alpha glycerol ... Reaction of proteases with starch, Reaction of lipases with starch , the reaction of phosphorylase with starch, the reaction of oxidase with starch, and the like. The enzyme modified starch may be prepared by using any combination of enzymatic treatments. An example of enzymatic modification of starch is the use of alpha-amylase enzymes to produce depolymerized starch. Reaction of cellulose with starch; Alpha-amylase-debranching enzyme to produce debranched starch. with starch; Reaction of proteases to produce starch with reduced protein content Reaction of lipase enzymes with starch; Use of lipase enzymes to produce starch with reduced lipid content Reaction of starch with phosphate; phosphorylase enzyme to produce enzyme-modified phosphorylated starch and the reaction of starch with oxidase enzymes to produce enzymatically oxidized starch. Including his reaction to Pun.
[0096] The disaccharide fatty acid ester may be a sucrose fatty acid ester according to formula I, wherein The "R" group is aliphatic, linear or branched, saturated or unsaturated, and has a molecular weight of from about 8 to about It has between 40 carbon atoms.
[0097] As used herein, "sugar fatty acid ester" and "sucrose fatty acid ester" refer to The term "sterile" refers to compositions having different purities and mixtures of compounds at any purity level. For example, the sugar fatty acid ester compound may be a substantially pure material, That is, a compound having a given number of "A" groups substituted with only one type of Structure I moiety is (i.e., all of the "R" groups are the same and all of the sucrose moieties are equal The sugar fatty acid ester compounds have different degrees of substitution. A blend of two or more sugar fatty acid ester compounds in which all of the substituents have the same "R" group structure. The sugar fatty acid ester compound may also be a compound having different degrees of "A" group substitution. The "R" group substituted moieties include compositions which are mixtures of compounds, and are comprised of two or more "R" groups of structure I. In a related embodiment, the "R" groups may be the same or For example, the sugar fatty acid esters in the composition may be the same. The sugar fatty acid esters may be the same or different (ie, a mixture of different sugar fatty acid esters).
[0098] Regarding the composition of the present invention, the composition is composed of a sugar fatty acid ester compound having a high degree of substitution. In an embodiment, the sugar fatty acid ester is polysoybean oil sucrose. It is. [ka]
[0099] Sugar fatty acid esters are prepared by the known process of esterification, with substantially pure fatty acids. Sugar fatty acid esters can also be made by esterification of sugars with natural sources, e.g. fatty acids derived from those found in oils extracted from oilseeds, such as soybean oil It can be prepared by transesterification using fatty acid esters in the form of glycerides. The transesterification reaction using fatty acid glycerides to provide sucrose fatty acid esters is e.g. For example, U.S. Patent No. 3,963,699; U.S. Patent No. 4,517,360; U.S. Patent No. No. 4,518,772; U.S. Pat. No. 4,611,055; U.S. Pat. No. 5,767,25 No. 7; U.S. Patent No. 6,504,003; U.S. Patent No. 6,121,440; and U.S. Patent No. As described in Patent No. 6,995,232 and International Publication No. WO 1992 / 004361, No. 6,393,962, which are incorporated herein by reference. .
[0100] In addition to producing hydrophobic sucrose esters by transesterification, the acid chloride was also converted to sucrose. Similar sparse copolymers can be obtained by reacting directly with polyols that contain a ring structure similar to that of cellulose. Hydraulic properties can be achieved in fibrous cellulosic articles.
[0101] As mentioned above, sucrose fatty acid esters are glycerides obtained from natural sources. It can be prepared by transesterification of sucrose from a methyl ester feedstock prepared from (See, e.g., U.S. Pat. No. 6,333,636, which is incorporated herein by reference. (See US Pat. No. 995,232.) As a result of the source of fatty acid, the amount of fatty acid used to prepare sucrose fatty acid esters is reduced. The raw materials used for this purpose are those having fatty acid moieties containing between 12 and 40 carbon atoms. It contains a series of saturated and unsaturated fatty acid methyl esters. In the resulting product, sucrose fatty acid ester, the sucrose moiety containing product is esterified. With reference to Structure I above, the "R" group is reflected in the form containing a mixture of sulfur moiety substituents. Between 12 and 26 in ratios reflecting the raw materials used to prepare the cellulose esters. To further illustrate this point, sucrose obtained from soybean oil is a mixture of sucrose and glycerol. Sodium ester is incorporated herein by reference. As described in the eventh Ed. Of the Merck Index, soybean oil Triglyceride of oleic acid (H3C-CH2]7-CH=CH-[C H2]7-C(O)OH), 49 wt.% linoleic acid triglyceride (H3C-[C H2]3-[-CH2-CH=CH]2-[-CH2-]7-C(O)OH), 11wt .% of linoleic acid triglyceride (H3C-[-CH2-CH=CH-]3-[-CH 2-]7-C(O)OH), and 14 wt.% triglycerides of various saturated fatty acids. All of these fatty acid moieties are a mixture of species with "R" group structures that reflect the , expressed as the "R" group of the substituent in the product sucrose fatty acid ester. Thus, As used herein, fatty acid raw materials obtained from natural sources such as soybean oil fatty acid sucrose are used. When sucrose fatty acid esters are referred to as the product of a reaction using The various components typically found as a result of the source from which the cellulose fatty acid esters are prepared. In a related embodiment, the sugar fatty acid ester as disclosed herein is The solvent has a low viscosity (e.g., about 10 to 2000 centipoise at room temperature or standard atmospheric pressure). In another embodiment, the unsaturated fatty acid may exhibit one, two, three or more It may have many double bonds.
[0102] In an embodiment of the invention, sugar fatty acid esters, and in some aspects disaccharide esters, The chain may have, on average, more than about 6 carbon atoms, about 8 to 16 carbon atoms, about 8 to about 18 carbon atoms, carbon atoms, from about 14 to about 18 carbon atoms, from about 16 to about 18 carbon atoms, from about 16 to Formed from fatty acids having about 20 carbon atoms, and from about 20 to about 40 carbon atoms. do.
[0103] In embodiments, the sugar fatty acid esters are hydrophobic, depending on the morphology of the cellulosic material. In one embodiment, sugar fatty acid esters (SFAs) may be present in different concentrations to achieve E) is attached as a coating on a cellulosic material, the SFAE is At least about 0.1 g / m2 on the surface of the system material 2 to about 1.0 g / m 2 , about 1.0g / m 2 to about 2.0 g / m 2 , about 2g / m 2 From about 3g / m 2 is present at a coating weight of 100%. In a related embodiment, the SFAE is about 3 g / m 2 From about 4g / m 2 , about 4g / m 2 from Approximately 5g / m 2 , about 5g / m 2 From about 10g / m 2 , about 10g / m 2 From about 20g / m 2 in In another embodiment, the cellulosic material may be a solution containing cellulose fibers. If so, the SFAE is at least about 0.025% (wt / wt) of the total fibers present. In a related embodiment, the SFAE is present at a concentration of about 0.05% ( 0.1% (wt / wt) to about 0.1% (wt / wt), 0.1% (wt / wt) to about 0.5% (wt / wt), about 0.5% (wt / wt) to about 1.0% (wt / wt), about 1.0% (wt / wt) to about 2.0% (wt / wt), about 2.0% (wt / wt) to about 3.0 %(wt / wt), about 3.0%(wt / wt) to about 4.0%(wt / wt), about 4.0 %(wt / wt) to about 5.0%(wt / wt), about 5.0%(wt / wt) to about 10 % (wt / wt), from about 10% (wt / wt) to about 50% (wt / wt). In further related embodiments, the amount of SFAE may be equal to the amount of fiber present. In some embodiments, the SFAE coats the entire exterior surface of the cellulosic material. (e.g., the entire paper or cellulose-containing article may be coated. stomach).
[0104] In another embodiment, the coating comprises about 0.5 wt / wt of coating. 9% to about 1.0%, about 1.0% to about 5.0%, about 5.0 to about 10%, about 10% to About 20%, about 20% to about 30%, about 40% to about 50% sugar fatty acid esters In a related embodiment, the coating comprises about It may contain from 25% to about 35% sugar fatty acid esters.
[0105] In embodiments, the cellulosic material may be, but is not limited to, paper, cardboard, paper Sheets, paper pulp, cups, boxes, trays, lids, release paper / liners, compost bags, shopping bags, shipping Shipping bags, bacon cardboard, tea bags, insulation, coffee or tea containers, pipes and water pipes, food grade disposable tableware, plates and bottles, TVs and portable devices screens for women, clothing (e.g., cotton or cotton blends), bandages, pressure-sensitive labels, pressure-sensitive tapes, Sexual products, as well as medical devices for use on or inside the body, e.g., contraceptives, drug delivery This includes devices, containers for pharmaceutical materials (e.g., pills, tablets, suppositories, gels, etc.), etc. The coating technology shown is applicable to furniture and interior decoration materials, outdoor camping equipment, etc.
[0106] In one embodiment, the coating as described herein has a molecular weight ranging from about 3 to about 9. In a related embodiment, the pH is within the range of about 3 to about 4. to about 5, from about 5 to about 7, from about 7 to about 9.
[0107] In an embodiment, for treating the surface of a cellulose-containing (or cellulosic) material The method of claim 1, further comprising the step of: A method is disclosed that includes applying a substance to a surface, R-CO-X Formula (II) X-CO-R-CO-X1 Formula (III) where R is a straight chain, branched chain, or cyclic aliphatic hydrocarbon having from 6 to 50 carbon atoms. X and X1 are independently Cl, Br, R-CO-OR, or O(CO ) OR, and when the alkanoic acid derivative comprises the formula (III), X or X1 are the same or Unlike the SFAE as disclosed herein, the SFAE is a carrier and the method is , no gaseous HCl, VOCs or catalysts are required.
[0108] In an embodiment, the alkanoic acid derivative is mixed with a sugar fatty acid ester to form an emulsion. and the emulsion is used to treat the cellulosic material.
[0109] In embodiments, the sugar fatty acid ester may be an emulsifier and may be one or more monoesters. No-, di-, tri-, tetra-, penta-, hexa-, hepta-, or octaesters In another embodiment, the fatty acid portion of the sugar fatty acid ester may comprise a mixture of saturated groups. , unsaturated groups, or combinations thereof. The emulsions containing, but are not limited to, milk proteins (e.g., casein, whey, Proteins, etc.), wheat gluten, gelatin, prolamins (e.g. corn zein) , soy protein isolate, starch, acetylated polysaccharides, alginate, carrageenan, Proteins including chitosan, inulin, long chain fatty acids, waxes, and combinations thereof; It may contain polysaccharides and / or lipids.
[0110] In embodiments, the sugar fatty acid ester emulsifier as disclosed herein is These include, but are not limited to, agarites, esters, diesters, ethers, ketones, amides , nitriles, aromatics (e.g., xylene, toluene), acid halides, anhydrides, talc , alkyl ketene dimer (AKD), alabaster, arganic acid, alum, albarin, Adhesive, barium carbonate, barium sulfate, chlorine dioxide, clay, dolomite, diethylenetriamine Amine pentaacetic acid, EDTA, enzymes, formamidine sulfate, guar gum, gypsum, lime, bisulfate Magnesium, milk of lime, milk of magnesia, polyvinyl alcohol (PvOH), rosin , rosin soap, satin, soap / fatty acid, sodium bisulfate, soda ash, titania, surfactant Agents, starches, modified starches, hydrocarbon resins, polymers, waxes, polysaccharides, proteins and combinations thereof, which carry coatings or other chemicals used in papermaking. It can be used to hold
[0111] In an embodiment, the cellulose produced by the method as disclosed herein is The cellulose-containing material exhibited greater hydrophobicity or water resistance than the untreated cellulose-containing material. In a related aspect, the treated cellulose-containing material is a cellulose-containing material without treatment. In a further related aspect, the material exhibits higher oleophobicity or grease resistance than the organic material. Therefore, the processed cellulose-containing materials are biodegradable, compostable, and / or recyclable. In one embodiment, the treated cellulose-containing material is hydrophobic (resistant to It is water-soluble (water-based) and oleophobic (grease-resistant).
[0112] In embodiments, the treated cellulose-containing material has improved properties compared to the same material that is untreated. For example, the process as disclosed herein may provide improved mechanical properties. The treated paper bags have increased burst strength, Gurley number, tensile strength and / or maximum In one embodiment, the burst strength is between about 0.5 and 1.0 times the energy of the load. Between about 1.0 and 1.1 times, between about 1.1 and 1.3 times, between about 1.3 and 1.5 times In another embodiment, the Gurley number is increased by between about 3 to 4 times, about 4 to 5 times In yet another embodiment, the increase is between about 5-6 fold and about 6-7 fold. The tensile stress is between about 0.5 and 1.0 times, between about 1.0 and 1.1 times, and between about 1.1 and 1.2-fold and between about 1.2-fold and 1.3-fold. The maximum load energy is between about 1.0 and 1.1 times, between about 1.1 and 1.2 times, The fold increase was between about 1.2 and 1.3 fold, and between about 1.3 and 1.4 fold.
[0113] In embodiments, the cellulose-containing material may be, for example, any of the cellulose-containing materials described in U.S. Patent Application Publication No. 2015 / 013666. No. 67243, which is incorporated herein by reference. Microfibrillated cellulose (MFC) or cellulose nanofibers (CNF) such as The base paper contains MFC or CNF, which is added during the molding and papermaking process. and / or a coating is applied to a previous forming layer to reduce the porosity of the base paper. In a related embodiment, the base paper is treated with a sugar fatty acid as described above. In a further related embodiment, the contacted base paper is further contacted with a poly ester. In an embodiment, the resulting contacted raw material is The paper is controllably water- and oil-resistant. The base paper has a Gurley value (i.e., Gurley air resistance ( sec / 100cc, 20oz.cyl.) or at least about 100, at least about 2 In one embodiment, the sugar fatty acid ester copolymer may exhibit a Gurley value of from about 300 to about 350. The coating may be a laminate of one or more layers or may be a laminate Alternatively, one or more layers may be provided by applying one or more layers of coating. The amount of rubber may be reduced to achieve the same performance benefits (eg, water resistance, grease resistance, etc.). In a related embodiment, the laminate is a biodegradable and / or compostable heat seal. The adhesive may include a binder or adhesive.
[0114] In embodiments, the sugar fatty acid ester may be formulated as an emulsion, optimally. The emulsifier and the amount used will depend on the nature of the composition and the ability of the drug to facilitate dispersion of the sugar fatty acid ester. In one embodiment, the emulsifier is determined by its ability to promote the , water, buffer, polyvinyl alcohol (PvOH), carboxymethylcellulose (CM C), milk protein, wheat gluten, gelatin, prolamin, soy protein isolate , starch, acetylated polysaccharides, alginate, carrageenan, chitosan, inulin, long chain Fatty acids, waxes, agar, alginates, glycerol, gums, lecithin, poloxamer , mono-, di-glycerol, monosodium phosphate, monostearate, propylene glycol Cole, detergent, cetyl alcohol, and combinations thereof. The ratio of sugar ester to emulsifier is from about 0.1:99.9, from about 1:99, to about 10:90 from, from about 20:80, from about 35:65, from about 40:60, and from about 50:50 The ratio may vary depending on the property(ies) desired in the final product. However, it will be apparent to those skilled in the art.
[0115] In embodiments, the sugar fatty acid esters may be used in conjunction with, but are not limited to, pigments (e.g., viscosity control). earth, calcium carbonate, titanium dioxide, plastic pigments), binders (e.g. starch, soy protein, polymer emulsion, PvOH), and additives (e.g., Glyco Xal, glyoxalated resin, zirconium salts, calcium stearate, oleic acid Cytin, polyethylene emulsion, carboxymethyl cellulose, acrylic polymer, Alginate, polyacrylate gum, polyacrylate, bactericide, oil-based defoamer, silicone Internal and surface sizing agents, including stilbenes, direct dyes and acid dyes. It may also be combined with one or more coating components (single or in combination) for coatings. In a related aspect, such components include, but are not limited to, microporous Builds structure, provides a light scattering surface, improves ink acceptance, improves gloss, binds pigment particles, and aids in paper Bonding coatings to the pigment, reinforcing the base sheet, filling pores within the pigment structure, reducing water sensitivity , wet pick resistance in offset printing, blade scratch prevention Improved gloss in supercalendering, reduced dust, controlled coating viscosity ,Providing water retention,Dispersing pigments,Maintaining coating dispersion,Coating / coating color prevention of damage to the coating, control of foaming, reduction of entrapped air and coating craters, whiteness and The optical filter may provide one or more features including increased brightness and color, as well as color and shadow control. It will be appreciated by those skilled in the art that the combination may vary depending on the property(ies) desired in the final product. It's obvious.
[0116] In embodiments, the methods of using the sugar fatty acid esters provide a desired property (e.g., tolerance). providing a layer of material that exhibits the same properties (water-based, low surface energy, etc.) to thereby achieve the same properties. By reducing the amount of primary / secondary layers required to complete the For example, silicone-based layer, starch-based layer, clay-based layer, PLA layer, PEI layer, etc. ) can be used to reduce the cost of application of the SFAE layer. In embodiments, the adhesive may be coated with a coating (e.g., a heat sealable agent). The composition is fluorocarbon-free and silicone-free.
[0117] In embodiments, the composition increases both the mechanical and thermal stability of the treated product. In one embodiment, the surface treatment is performed by thermal annealing at a temperature between about -100°C and about 300°C. In a further related embodiment, the surface of the cellulosic material is at about 60° to In another related embodiment, the surface treatment exhibits a water contact angle of between about 200° C. It is chemically stable at temperatures between about 300°C and about 300°C.
[0118] The substrate, which may be dried (e.g., at about 80-150° C.) before application, may be, for example, dipped into the surface and The substrate may be treated with the modifying composition by exposing the surface to the composition for less than a second. It may be heated to dry, after which the modified material is ready for use. According to the method as disclosed herein, the substrate is typically manufactured in a paper mill. The coating / sizing process may be carried out in any suitable manner (e.g., Smook, G., Sur face treatments in Handbook for Pulp&Pap er Technologists,(2016),4 th Ed.,Cpt.18,p p.293-309, TAPPI Press, Peachtree Corners, See GA USA).
[0119] No special preparation of materials is required in the practice of the present invention, however, in some applications, The material may be dried prior to processing. In embodiments, the methods as disclosed include, but are not limited to, Any cellulosic material, including but not limited to films, rigid containers, fibers, pulps, fabrics, etc. In one embodiment, the sugar fatty acid ester or coating agent may be used on the surface of the , conventional size press (vertical type, inclined type, horizontal type), gate roll size press, metal calendering size press, calendering size application, tube sizing, on-machine , off-machine, single-sided coater, double-sided coater, short dwell, simultaneous double-sided coater, Blade or rod coater, gravure coater, gravure printing, flexographic printing, ink Applied by jet printing, laser printing, supercalendering and combinations thereof It can be done.
[0120] Depending on the source, cellulose can be used in paper, cardboard, pulp, softwood fibers, hardwood fibers, or or combinations thereof, nanocellulose, cellulose nanofibers, whiskers or micro Fibril, microfibrillated, cotton or cotton blends, cellulose nanocrystals, or nano It may also be fibrillated cellulose.
[0121] In an embodiment, the amount of sugar fatty acid ester coating applied is It is sufficient to completely cover at least one surface of the material. The sugar fatty acid ester coating may be applied to the entire exterior surface of the container, the entire interior surface of the container, or both. A combination of these may be applied to one or both sides of the base paper. In some embodiments, the entire upper surface of the film may be coated with a sugar fatty acid ester coating. or the entire lower surface of the film may be covered with a sugar fatty acid ester coating; and In some embodiments, the device / appliance routing may be The device / instrument may be coated with a coating or the outer surface of the device / instrument may be coated with a sugar fatty acid. It may be coated with an ester coating, or a combination thereof. In an embodiment, the amount of sugar fatty acid ester coating applied is The amount of the coating that is applied is sufficient to partially coat at least one surface of the material. Only the exposed surfaces are covered with a sugar fatty acid ester coating or exposed to ambient air. Only surfaces that are not exposed to the air are coated with a sugar fatty acid ester coating (e.g. As will be appreciated by those skilled in the art, the sugar fatty acid ester coating applied The amount may depend on the use of the material being coated. In one embodiment, one surface is coated with sugar fatty acid ester. The opposite surface may be coated with, but is not limited to, a protein, Wheat gluten, gelatin, prolamin, soy protein isolate, starch, modified starch Pu, acetylated polysaccharides, alginate, carrageenan, chitosan, inulin, long-chain fatty acids The surface of the surface of the substrate may be coated with agents including glycerides, waxes, and combinations thereof. In such a case, SFAE may be added to the furnish and the resulting material on the web may be coated with SFA. An additional coating of E may be provided.
[0122] In the course of practicing this aspect of the method, any suitable coating process may be used to coat the Any of a variety of sugar fatty acid ester coatings and / or emulsions that are applied to the In an embodiment, the sugar fatty acid ester coating process can include: The present invention may be used alone or in combination with other coating processes adapted to practice the methods as disclosed. process, along with impregnation, spraying, painting, printing, and any combination of any of these processes. This includes.
[0123] For example, by increasing the concentration of sugar fatty acid esters, Such compositions also exhibit improved water / lipid resistance properties, with the end result being that they are easily processed. However, at higher coat weights, the cellulose may react more extensively with the cellulose being treated. In one embodiment, various catalysts This allows for a more rapid and precise adjustment of the amount of sugar fatty acid ester to suit a particular application. This may allow for a more precise "hardening."
[0124] The selection of the cellulose to be treated, the sugar fatty acid ester, the reaction temperature, and the exposure time determine the final Process parameters can be optimized by routine experimentation to suit any particular application of the product. It will be apparent to those skilled in the art that the parameters are
[0125] The derivatized material may be clarified and analyzed using appropriate tests known in the art. For hydrophobicity, the analysis protocol is These may include, but are not limited to, contact angle measurements and moisture pick-up. Includes stiffness, WVTR, porosity, tensile strength, lack of substrate degradation, burst and tear properties The specific standardized protocols to be followed are set out by the American Society for Testing and Materials (ASMT). As defined by the International Standards Board for Testing and Materials (ISBN) (Protocol ASTM D7334-08).
[0126] The permeability of the surface to various gases, such as water vapor and oxygen, also improves the barrier function of the material. The membrane can be modified by a sugar fatty acid ester coating process to increase the permeability. The standard unit for measuring these parameters is the barrer, and protocols for measuring these parameters are also available. and is available in the public domain (ASTM Standard F2476-0 for water vapor). 5 and ASTM standard F2622-8 for oxygen).
[0127] In embodiments, materials treated according to the procedures of the present disclosure can be used in environments under microbial challenge. It exhibits complete biodegradability as measured by the breakdown of
[0128] The shake flask method (ASTM E1279-89( 2008)) and the Zahn-Wellens test (OECD TG 302B) A variety of methods are available.
[0129] Compostability determination and testing includes, but is not limited to, ASTM D6400 There are various methods available.
[0130] Materials suitable for treatment by the process of the present invention include various forms of cellulose, such as cotton fibers. , vegetable fibres, e.g. flax, wood fibres, regenerated cellulose (rayon and cellophane), Partially alkylated cellulose (cellulose ether), partially esterified cellulose (acetate Trayon), and other modified ceramics where a substantial portion of the surface is available for reaction / bonding. As mentioned above, the term "cellulose" includes these materials. This includes all other materials having similar polysaccharide structures and similar properties. A relatively new material, microfibrillated cellulose (cellulose nanofibers) (e.g., No. 4,374,700, which is incorporated herein by reference. No. 2 and U.S. Patent Application Publication Nos. 2015 / 0167243 and 2009 / 02 21812) are particularly suitable for this application. Examples of cellulose acetate include, but are not limited to, cellulose triacetate, cellulose propionate, and cellulose acetate. Cellulose pionate, cellulose acetate butyrate, nitrocellulose (cellulose nitrate), sulfuric acid Cellulose, celluloid, methyl cellulose, ethyl cellulose, ethyl methyl cellulose cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, cellulose nanocrystals , Hydroxyethyl methylcellulose, Hydroxypropyl methylcellulose, Ethyl hyd hydroxyethyl cellulose, carboxymethyl cellulose, and combinations thereof. obtain.
[0131] The modification of cellulose as disclosed herein also increases its hydrophobicity. , its tensile strength, flexibility and stiffness can be increased, thereby expanding its range of use. The modified cellulose disclosed in this application can be further expanded. or all biodegradable and partially biodegradable products made therewith, Including recyclable and compostable products is within the scope of this disclosure.
[0132] Among the possible applications of coating technology, such items include, but are not limited to: containers for all purposes, e.g. paper, cardboard, paper pulp, cups, lids, boxes, trays, release paper / Liners, compost bags, shopping bags, pipes and conduits, food grade disposable tableware, plates and and bottles, screens for TVs and mobile devices, clothing (e.g. cotton or cotton blends), Bandages, pressure sensitive labels, pressure sensitive tapes, feminine products, and medical products used on or inside the body Devices such as contraceptives, drug delivery devices, etc. The coating techniques may be used in furniture and upholstery materials, outdoor camping equipment, and the like.
[0133] The following examples are intended to illustrate, but not limit, the present invention. . EXAMPLES
[0134] [Example 1] Sugar fatty acid ester formulation SEFOSE® is a liquid at room temperature and all coatings containing this material The coating / emulsion was applied at room temperature using a benchtop drawdown device. Rod types and sizes were varied to produce a range of weights.
[0135] Mixture 1 195 ml of water and 5 grams of carboxymethylcellulose (FINNFIX®) To a solution containing 50 mL of CP Kelco (Atlanta, GA) SEFOSE® was added. Silverson set at 5000 rpm The formulation was mixed for 1 minute using a homogenizer. On a 50 gram base sheet and an 80 gram sheet of unbleached softwood, Both papers were placed in an oven (105°C) to dry. After removing from the oven, the sheets were placed on the laboratory bench and pipette was applied to each sheet. Ten drops of water (room temperature) were dropped onto the base sheet. The base sheet selected for this test absorbed the water droplets immediately. whereas sheets coated with various amounts of SEFOSE® showed Increasing sample weights exhibited increasing levels of water resistance (see Table 1).
[0136] [Table 1]
[0137] Water resistance is lower in heavier sheets, and water resistance is not achieved unless the sheet is dried. It was observed that this was not the case.
[0138] Mixture 2 Addition of SEFOSE® to cup stock: (This is a monolayer without MFC treatment) Note that the stock is 110 gram cardboard made from eucalyptus pulp. 50 grams of SEFOSE® was mixed with 200 grams of 5% heat-treated ethylated decanter. Starch (Ethylex 2025) was added and mixed for 30 seconds using a benchtop kady mill. The paper samples were coated and placed in a 105°C oven for 15 minutes. 10 to 15 drops of the test liquid were dropped onto the side of the test piece, and the water resistance time was measured and recorded in the table below. Water penetration in the treated cardboard control was immediate (see Table 2).
[0139] [Table 2]
[0140] Mixture 3 Pure SEFOSE® was warmed to 45° C. and placed in a spray bottle. A uniform spray was applied to the paper stocks listed in the above, as well as to pieces of fiberboard and a quantity of cotton fabric. When a drop of water was dropped onto the sample, it penetrated into the substrate within 30 seconds, but it took 1 After drying in the oven for 5 minutes, the water beads evaporated before being absorbed into the substrate.
[0141] Subsequent studies have demonstrated that SEFOSE® is an oil and grease resistant coating. The question was whether it was compatible with the compounds used. ) is useful for improving water resistance and stiffness. Using 240 gram cardboard stock, Stiffness testing was performed. Table 3 shows the results. These data are based on a stiffness test of 5 grams per square meter. Although a single coat weight was obtained, the average of five samples is reported. 5 Taber stiffness units recorded on a Taber stiffness tester Model 150-E.
[0142] [Table 3]
[0143] [Example 2] Attachment of sugar esters to cellulosic substrates In order to determine whether SEFOSE® reversibly binds to cellulosic materials, For example, pure SEFOSE® was mixed with pure cellulose in a 50:50 ratio. The SEFOSE® was reacted at 300°F for 15 minutes and the mixture was diluted with methylene chloride. (non-polar solvent) or distilled water. The samples were refluxed for 6 hours and the samples were gravimetrically analyzed. .
[0144] [Table 4]
[0145] [Example 3] Inspection of cellulosic surfaces Scanning electron microscope images of base paper with and without MFC show that the less porous base This illustrates how paper may require a much lower amount of waterproofing agent to react with the surface. Figures 1-2 Figure 1 shows the untreated medium porosity Whatman filter paper. Figures 1 and 2 show the reaction of the derivatizing agent. This indicates a relatively high exposed surface area for water to escape, but also provides ample space for water to escape. Figures 3 and 4 show the coating in the MFC. A side-by-side comparison of paper made from recycled pulp before and after processing is shown. These are two magnified views of the same sample, but clearly the left side of the image is missing the MCF. showed that derivatization of much less porous sheets showed promise for long-term water / vapor barrier performance. The last two images are simply the average of the number of particles on a sheet of filter paper. A close-up of the target “pores” and a similar close-up of a CNF-coated paper for comparison. It is.
[0146] The data above show that the addition of more material results in a corresponding increase in performance. Without being bound by theory, the reaction appears to be faster on unbleached paper. This suggests that the presence of lignin may accelerate the reaction.
[0147] Products such as SEFOSE® are liquid and easily emulsifiable. Easily adaptable to work with coating equipment commonly used in paper mills This suggests that:
[0148] [Example 4] "Phluphi" Liquid SEFOSE® is mixed and reacted with bleached hardwood fibers to produce a waterproof handsheet. This has led to a variety of techniques for forming paper. It was found that when mixed with the fiber, the majority of the cellulose was retained with the fiber. Drying produced a brittle, fluffy, but very hydrophobic handsheet. 0.25 grams of SEFOSE® in 6 liters of water. The mixture was hand stirred and the water was removed in a standard handsheet mold. The resulting fiber mat was removed and dried at 325° F. for 15 minutes. The sheets exhibited significant hydrophobicity and greatly reduced hydrogen bonding between the fibers. The water contact angle was observed to be greater than 100 degrees.) An emulsifier may be added. SEF The OSE® to fiber ratio may be about 1:100 to 2:1.
[0149] Subsequent testing has shown that talc is merely a spectator here. and were excluded from further testing.
[0150] [Example 5] Environmental Effects on SEFOSE® Coating Properties In order to better understand the mechanism of sucrose ester reaction with fibers, a low viscosity coagulant was Coating is a bleached cloth with wet strength resins but no water resistance (no sizing). All coatings were measured using a Brookfield viscometer. When measured at 100 rpm it was less than 250 cps.
[0151] SEFOSE® was emulsified with Ethylex 2025 (starch) and granulated. The paper was coated with a via roll. For comparison, SEFOSE® was also coated with Westco The emulsion was then emulsified with TE 9050 PvOH. The oxidation of the double bond in ) is driven by heat and the presence of an additional chemical environment that enhances the oxidation chemistry. (see also Table 5).
[0152] [Table 5]
[0153] [Example 6] Effect of unsaturated vs. saturated fatty acid chains SEFOSE® is reacted with bleached softwood pulp and dried to form a sheet. Subsequent extractions with CH2Cl2, toluene, and water were performed to determine the extent of reaction with the pulp. The extraction was carried out using a Soxhlet extraction glass apparatus for at least 6 hours. The results are shown in Table 6.
[0154] [Table 6]
[0155] The data indicates that essentially all of the SEFOSE® remains in the sheet. To further verify this, the same procedure was carried out on the pulp alone, and the results were The results indicate that approximately 0.01 g of cellulose was obtained per 10 g of pulp. This is due to residual pulping chemicals, or rather extractives that have not been completely removed. It can be easily explained as:
[0156] Cellulose (e.g., α-cellulose from Sigma Aldrich, St. Louis, MO) The experiment was repeated using pure fibers of cellulose. As long as the input level remains below about 20% of the fiber mass, the SEFOSE® mass More than 95% of the cellulose was retained with the fiber and was not extractable with polar or non-polar solvents. However, by optimizing the baking time and temperature, the residual cellulose may be removed with the fibers. The amount of sucrose esters that can be distilled off can be further increased.
[0157] As shown, the data shows that it is possible to extract SEFOSE® from the material after drying. On the other hand, the study demonstrated that it is generally impossible to extract fats that contain all saturated fatty acid chains. When acid is used in place of SEFOSE® (e.g., Procter & Ga OLEA available from Amble Chemicals (Cincinnati, OH) N®), nearly 100% of the material can be extracted using hot water (above 70°C). OLEAN® is identical to SEFOSE® with the only change being , saturated fatty acids (OLEAN®) instead of unsaturated fatty acids (SEFOSE®) The problem is that the mark (trademark) is attached.
[0158] Another notable aspect is that multiple fatty acid chains are linked to the cellulose and two sugar molecules within the structure. Being reactive, SEFOSE® creates a rigid crosslinked network and in fibrous webs such as paper, cardboard, airlaid and wet-laid nonwovens, and fabrics. This results in improved strength.
[0159] [Example 7] Addition of SEFOSE® to achieve water resistance 2-gram and 3-gram hand-made paper using both hardwood and softwood kraft pulp. Paper was made using a 1% pulp slurry with SEFOSE® at levels above 0.1%. When the water is drained off to form the handsheet, SEFOSE® remains with the fibers. At 0.1% to 0.4% SEFOSE®, the Beaded up on the surface for a few seconds. SEFOSE® dosage was greater than 0.4%. After addition of 1.5%, the time for water resistance increased rapidly to several minutes and then increased to 1.5% above the loading level. increased to several hours.
[0160] [Example 8] Creation of bulky fibrous materials Adding SEFOSE® to pulp softens the fibers and increases the space between them. For example, a pulp containing 125 g (dry) A 3% slurry of hardwood pulp is drained and dried to produce a volume of 18.2 cubic centimeters. It was found that 12.5 g of SEFOSE® was mixed with the equivalent of 125 g. The mixture was added to the same 3% hardwood pulp slurry containing 100% dry fiber. The water was drained off and the mixture was dried. After cooling, the resulting mat occupied 45.2 cubic centimeters.
[0161] 30g of standard bleached hardwood kraft pulp (Old Town Fuel and Fiber, LLC, Old Town, ME) and heated to 60°C. (registered trademark) was sprayed onto this 4.3 cm 3 The mixture was placed in a crusher at 10,000 rpm and the essence was The mixture was poured into a handsheet mold and dried at 105°C. The pulp is 8.1 cm 3 A 2 inch square piece of this material was cut. The squares were then placed in a hydraulic press and subjected to 50 tons of pressure for 30 seconds. The volume of the squares was significantly reduced. The thickness was reduced, but still less than the same 2-inch square piece cut as a control with no pressure applied. It occupied more than 50% of the volume.
[0162] Increased bulk and flexibility was observed as well as forced repulping when the water was drained. It is important that the mat result in a fiber mat in which all of the hydrophobic properties are retained. The observation is that water cannot be easily "pushed" through the sheet over a low surface energy barrier. This is an additional benefit of the observation that the attachment of hydrophobic single chains of fatty acids does not exhibit this property.
[0163] Without being bound by theory, this is believed to be due to the SEFOSE® reacting with cellulose. and the OH groups on the surface of the cellulose fibers are available to participate in subsequent hydrogen bonds. This provides further evidence that other hydrophobic materials interfere with the initial hydrogen bond. However, after repulping, this effect is reversed, and the OH groups on the cellulose form hydrogen bonds after redrying. Free to engage.
[0164] [Example 9] Bag paper test data The following table (Table 7) shows the results of the blending of SEFOSE® with unbleached kraft bag stock (control). and polyvinyl alcohol (PvOH) mixture at 5-7 g / m 2 Coating with The characteristics imparted by the above are shown. A commercially available bag is also included for reference.
[0165] [Table 7]
[0166] As can be seen in the table, the tensile and burst were significantly higher for SEFOSE® and It increases with coating of the control base paper with PvOH.
[0167] [Example 10] Wet / Dry Tensile Strength Three gram handsheets were made from bleached pulp. The following were prepared using different levels of SEFOSE: The wet and dry tensile strengths of these handsheets are compared with those of the handsheets with the addition of 1,2,3,4-trimethylsiloxane. SEFOSE® is not emulsified into any coating, but simply mixed into the pulp. Note that these were discharged without any other chemicals added (see Table 8). .
[0168] [Table 8]
[0169] Also, the 5% addition for wet strength did not significantly reduce the dry strength of the control. I want to be loved.
[0170] [Example 11] Use of esters containing less than eight saturated fatty acids Sucrose esters produced with less than eight fatty acids attached to the sucrose moiety Several experiments were performed with the model, with 50, 10, 1 and essentially 0% SP50, SP10, SP01 and F20W (Sisterna These commercial products are sucrose saturated are made by reacting with hydrated fatty acids, thus avoiding further cross-linking or similar chemical reactions. These are less useful for applications but are useful for testing emulsification and water repellency properties.
[0171] For example, 10 g of SP01 and 10 g of glyoxal in a 10% heat-treated PvOH solution The mixture was "heat treated" at 200°F for 5 minutes and made from bleached hardwood kraft. The coating was applied by drawdown to a porous base paper that had been coated with a crosslinked wax-like coating. A coating was obtained, which showed good hydrophobicity. 2 When applied, The contact angle measured was more than 100°. Glyoxal is used for compounds with OH groups. This method utilizes the residual alcohol groups on the sucrose ring, as these are well-known crystallization materials used in with alcohol groups available in the substrate or other coating material. This is a potential means of attaching highly unreactive sucrose esters to surfaces.
[0172] [Example 12] HST Data and Moisture Absorption To demonstrate that only SEFOSE® provides the waterproofing properties observed , porous Twins River (Matawaska, ME) base paper was mixed with various amounts of SEF OSE (and PvOH or Ethylex 2025 for emulsification, for drawdown The samples were treated with 100% ethanol (applied by a 5000 ethanol spray) and analyzed by the Hercules size test. The results are shown in Table 9.
[0173] [Table 9]
[0174] As can be seen in Table 9, the amount of SEFOSE® applied to the surface of the paper The increase results in increased water resistance (as indicated by an increased HST expressed in seconds).
[0175] This is also seen with saturated sucrose ester product coatings. In this particular example, the product F20W (Sisterna, The Nethe (available from Rlands) has a very low percentage of 4-8 substitutions with most molecules in the range. Described as a monoester. The pick-up of F20W products creates a stable emulsion. Equal parts of each were used to emulsify with PvOH to prepare the coating. Note that the pickup is only 50%. 2 ", the same PvOH pickup is also present and is 1.0 g / m 2 of The results are shown in Table 10.
[0176] [Table 10]
[0177] As can be seen from Table 10, again, the increase in F20W increases the water resistance of the porous sheet. Therefore, the applied sucrose fatty acid ester itself increases the water resistance of the paper. It is set to.
[0178] Water resistance is not only due to the presence of fatty acids that form ester bonds with cellulose. Considering that SEFOSE® is not a The oleic acid was added directly to the pulp, but the oleic acid reacted with the cellulose in the pulp. The mass at time zero was measured by hand after removal from a 105°C oven. This represents the "bone dry" weight of the paper. The samples were placed in a humidity controlled room maintained at 50% RH. The change in amount was recorded over time (in minutes) and the results are shown in Tables 11 and 12.
[0179] [Table 11]
[0180] [Table 12]
[0181] Here, when oleic acid is added directly to the pulp, the formation of ester bonds significantly reduces moisture absorption. In contrast, only 2% of SEFOSE® absorbs moisture. At higher concentrations, SEFOSE® does not inhibit moisture absorption. Without being bound by theory, the structure of the SEFOSE® binding material is a simple fatty acid ester. It cannot be simply explained by the structure formed by steel and cellulose.
[0182] [Example 13] Saturation SFAE The saturated class of esters are waxy solids at room temperature, which means that due to saturation, Less reactive with the material matrix or with itself. High temperatures (e.g. at least 40°C, At temperatures above 65°C (all tested), these materials melt and become liquid. The coating may be applied in a hydrophobic solution, which is then cooled and solidifies to form the hydrophobic coating. These materials are then emulsified as solids and applied as water-based coatings to impart hydrophobic properties. Sex may be imparted.
[0183] The data presented here was obtained from papers coated with various amounts of saturated SFAE. The HST (Hercules Size Test) readings are shown.
[0184] #45, bleached hardwood kraft sheet obtained from Turner Falls Paper, was used in the test. The Gurley porosity was measured to be approximately 300 seconds, making it a very dense coating. The base sheet is S-370 obtained from Mitsubishi Foods (Japan) It was previously emulsified with xanthan gum (up to 1% of the mass of the saturated SFAE formulation).
[0185] Coat weight (lbs per ton) of saturated SFAE formulation HST (4 runs per sample) constant average).
[0186] [Table 13]
[0187] The experimental data generated also demonstrated that the limited amount of saturated SFAE could be designed for other purposes / uses. For example, the saturated S FAE blends Ethylex starch and polyvinyl alcohol based coatings The coatings were then washed with water and in each case an increase in water resistance was observed.
[0188] The following example is a bleached recycled #50 with a Gurley porosity of 18 seconds. Coated on a base.
[0189] 100 grams of Ethylex 2025 was heat treated at 10% solids (1 liter volume). The mixture was then mixed with 10 grams of S-370 at high temperature and homogenized using a Silverson homogenizer. The resulting coating was then drawn down using a standard benchtop drawdown device. and the paper was dried under a heat lamp.
[0190] At 300# / ton coat weight, starch alone had an average HST of 480 seconds. At the same coat weight for starch and saturated SFAE mixture, the HST increased to 710 seconds. Ta.
[0191] Dissolve enough polyvinyl alcohol (Selvol 205S) in warm water to make a 10% solution. This solution was coated onto the same #50 paper as above and achieved 150 lb / ton. This same solution was used to prepare S-370 and S-400. Add 90% PVOH / 10% S-370 on a dry basis (i.e., 90 ml of water, 9 A mixture containing 1 g PvOH and 1 g S-370 achieved an average HST increased to 380 seconds.
[0192] Saturated SFAEs are derived from prolamins (specifically, zein, which is incorporated herein by reference). See U.S. Patent No. 7,737,200, the disclosure of which is incorporated herein by reference. One of the major obstacles to commercial production of the subject matter of the patent is that the formulation is water soluble. Thus, the addition of saturated SFAE helps.
[0193] [Example 14] Other saturated SFAEs A bleached lightweight sheet (approximately 35#) that had no sizing and had relatively low moldability Size press evaluations of saturated SFAE basecoats were performed against the SFAE basecoats. All evaluations were performed Exceval HR 3010 PvO heat treated to emulsify saturated SFAE H. Sufficient saturated SFAE was added to account for 20% of the total solids. The focus was on the evaluation of S-370 versus C-1800 samples (available from Mitsubishi Foods, Japan). Both of these esters performed better than the control, but some of the key data are presented. Shown in Figure 14.
[0194] [Table 14]
[0195] Saturated compounds showed an increase in kit, and both S-370 and C-1800 showed an increase in HST Note that this appears to result in about a 100% increase in
[0196] [Example 15] Wet Strength Additives Laboratory testing has demonstrated that sucrose ester chemistry is suitable for use as a wet strength additive. It has been shown that the saturated groups can be tuned to achieve a variety of properties. by attaching it to each alcohol functional group on sucrose (or other polyol). When esters are made, they become hydrophobic, waxy, and have low miscibility / solubility in water. The resulting substrate is water resistant, either internally or as a coating. Although cellulosic materials may be added to the sample to facilitate separation, they may not be compatible with each other or with the sample matrix. Since they do not chemically react with any part of the material, they can be removed by solvents, heat and pressure. It's easy to get eliminated.
[0197] If waterproofing and a higher level of water resistance are desired, sucrose esters may be added to the matrix. 4. Helps immobilize the polymer and makes it highly resistant to removal by physical means; For the purpose of achieving oxidation and / or crosslinking, sucrose containing unsaturated functional groups is used. Sugar esters can be made and added to cellulosic materials. By adjusting the size of the ester, strength is imparted and water resistance is also imparted. This provides a means for cross-linking using molecules that are not optimal for the intended application.
[0198] The data presented here compares the effect of varying levels of SEFOSE® on bleached kraft steel. The percentages shown in the table are measured by adding the cellulose acetate to the mixture and obtaining wet tensile data. The percentages represent the percent sucrose esters of the treated 70# bleached paper (see Table 15). reference).
[0199] [Table 15]
[0200] The data show that the addition of unsaturated sucrose esters to paper increases the The dry tensile strength of the sheet is shown to increase with increasing wet strength. Shows great strength.
[0201] [Example 16] A method for producing sucrose esters using acid chlorides. In addition to producing hydrophobic sucrose esters by transesterification, the acid chloride was also converted to sucrose. Similar sparse copolymers can be obtained by reacting directly with polyols that contain a ring structure similar to that of cellulose. Hydraulic properties can be achieved in fibrous articles.
[0202] For example, 200 grams of palmitoyl chloride (CAS 112-67-4) can be mixed with 50 grams of The mixture was mixed with sucrose and mixed at room temperature. After mixing, the mixture was brought to 100°F and then cooled to 100°C. The resulting material was washed with acetone and deionized water and optionally The remaining material was analyzed using C-13 NMR. showed that large amounts of hydrophobic sucrose esters were produced.
[0203] It has been shown that the addition of fatty acid chlorides to cellulosic materials can impart hydrophobic properties (BT3 and As shown by others, the by-product gaseous HCl is released into the surrounding material. This can cause several problems, including corrosion of the However, the reaction itself is undesirable in situ. One additional problem posed by the production of hydrochloric acid is The problem is that the more polyol moieties are formed, i.e. the more reacted the fiber becomes. Palmitoyl chloride is a compound that is effective in reducing the fiber composition of cellulose and cotton. As increasing amounts of the material reacted with the material and the hydrophobicity increased, the strength of the article decreased.
[0204] The above reactions were carried out on corn starch, xylan from birch, carboxymethylcellulose, 50 grams each of other similar products containing cellulose, glucose and extracted hemicellulose The reaction was repeated several times using 200 grams of R-CO-chloride reacted with 100 grams of polyol.
[0205] [Example 17] Peel test The peel test measures the force required to peel the tape from a paper surface at a reproducible angle. To determine the strength of the tensile tester, a wheel is used between the two jaws of the tensile tester (ASTM D18 76;For example, 100 Series Modular Peel Tester, Te stResources, Shakopee, MN).
[0206] For this work, the Turner Falls paper (Turner's Falls, MA) A) was used as the bleached kraft paper with high Gurley (600 sec). The 0 pound sheet represents a very dense yet highly absorbent sheet.
[0207] #50 pound paper coated with 15% Ethylex starch as a control The average force required (across five samples) was 0.55 lbs / in. The same coating, but with 25% Ethylex starch added to SEFOSE (registered trademark) (So 25% of the pickup is SEFOSE®, When treated with a coating (75% still Ethylex), the average force was 0. 50% of the Ethylex was replaced with SEFOSE®. When replaced with , the force required was reduced to less than 0.03 pounds per inch.
[0208] The paper preparation follows TAPPI Standard Method 404 for the determination of tensile strength of paper.
[0209] Finally, the same paper was used with the S-370 at an input rate of 750 pounds per ton, This effectively fills all the pores in the sheet, forming a complete physical barrier. does indeed pass the TAPPI kit 12 on a flat surface. This simple experiment shows that saturated SFA This shows that it is possible to obtain grease resistance using E type.
[0210] Other uses The cup base stock is heavily treated with rosin to increase water resistance. However, Gurley on this cardboard is known to be 50 seconds. This indicates that it is a highly porous cardboard. This cardboard is made of pure SEFO. The material was coated with SE and dried overnight in an oven at 100°C. The material had a 50% (wt / wt) water-resistant, water-repellent feel and was completely waterproof. ) cellulose / 50% (wt / wt) SEFOSE®. Gurley The temperature was too high to measure. Immersion of the sample in water for 7 days did not significantly soften the material. However, according to greenhouse data, biomass was determined in approximately 150 days. It appears that common tapes and adhesives do not stick to this composite material.
[0211] Zein has been shown to impart grease resistance to paper, so saturated SFAE and zein The stable aqueous dispersion of zein with 2 to 5% saturated SFAE was Observations showed that saturated SFAE produced a grease-resistant liquid (up to 25% in water). It has been demonstrated that zein can be "sealed" onto paper, imparting water resistance (in addition to water resistance) .
[0212] Although the invention has been described with reference to the above examples, modifications and variations are intended to fall within the spirit and scope of the invention. It is understood that what is claimed is within the scope of the following claims. All references disclosed herein are hereby incorporated by reference. This is intended to form part of the description of the specification.
Claims
1. A composition comprising a sugar fatty acid ester (SFAE) bound cellulosic material, the SFAE bound cellulosic material being a film or paper, the SFAE being present at a concentration such that the bound cellulosic material exhibits a water contact angle greater than 90°, the water contact angle being measured by an optical tensiometer, and the SFAE being present at a concentration of at least 0.025% (wt / wt) of total cellulose fibers present in the film or paper.
2. 2. The composition of claim 1, wherein the sugar fatty acid ester contains at least one sugar and at least one aliphatic group containing from 6 to 30 carbons, and the sugar is a disaccharide selected from the group consisting of raffinose, maltodextrose, a disaccharide containing galactose, a disaccharide containing sucrose, a disaccharide containing glucose, a disaccharide containing fructose, a disaccharide containing maltose, a disaccharide containing mannose, a disaccharide containing erythrose, isomaltose, isomaltulose, trehalose, trehalulose, cellobiose, laminaribiose, chitobiose, and combinations thereof.
3. The composition of claim 2 wherein the aliphatic group is derived from a natural source.
4. 4. The composition of claim 3, wherein the natural source is an oil seed, the SFAE is sucrose soybean oil fatty acid, and the fatty acid chains are selected from the group consisting of oleic acid, linoleic acid, linolenic acid, and combinations thereof.
5. The composition of claim 3 wherein the aliphatic group contains a mixture of saturated and unsaturated bonds.
6. 10. The composition of claim 1, wherein the cellulosic material further comprises microfibrillated cellulose (MFC), nanofibrillated cellulose, or cellulose nanocrystals.
7. 10. The composition of claim 1, further comprising a compound selected from the group consisting of polyvinyl alcohol (PvOH), polylactic acid, clay, talc, starch, glyoxyl, prolamine, and combinations thereof.
8. 2. The composition of claim 1, wherein the sugar fatty acid ester is a mono-, di-, tri-, tetra-, penta-, hexa-, hepta-, octa-ester or mixtures thereof, and the composition comprises one or more sugar fatty acid esters having a combination of saturated and unsaturated fatty acids.
9. The composition of claim 1 , which is biodegradable and / or compostable.
10. 10. The composition of claim 1, wherein the film or paper is selected from the following forms: food storage cartons, lids, food storage bags, weed control / barrier fabrics or films, mulching films, flower pots, filler beads, bubble wrap, oil absorbent materials, laminates, envelopes, gift cards, credit cards, gloves, raincoats, OGR paper, shopping bags, shipping bags, insulation, membranes, bacon cardboard, diapers, tea bags, tea or coffee containers, compost bags, release paper, tableware, containers for holding hot or cold beverages, cups, dishes, bottles for storing carbonated liquids, bottles for storing non-carbonated liquids, food packaging films, garbage disposal containers, food handling equipment, textile fibers, water storage and transport equipment, storage and transport equipment for alcoholic or non-alcoholic beverages, exterior casings or screens for electronic products, interior or exterior parts of furniture, curtains, upholstery materials, films, boxes, sheets, trays, pipes, water conduits, clothing, medical devices, contraceptives, pharmaceutical packaging, camping equipment, molded cellulosic materials, and combinations thereof.
11. 10. The composition of claim 1, wherein the sugar fatty acid ester contains one or more functional groups selected from ether, ester, thio, amino, phospho, or combinations thereof.
12. 1. A method for controllably derivatizing a cellulosic material for water resistance, comprising: a) contacting the cellulosic material with a formulation that confers water resistance, the formulation comprising a sugar fatty acid ester (SFAE); b) binding the sugar fatty acid esters onto a surface of the cellulosic material to obtain the water-resistant SFAE-bound cellulosic material; Including, the SFAE-bonded cellulosic material is a film or paper; the water resistance corresponds to a water contact angle of greater than 90°; the water contact angle was measured by an optical tensiometer; The method, wherein the SFAE is present at a concentration of at least 0.025% (wt / wt) of total cellulose fibers present in the SFAE-bound cellulosic material.
13. 13. The method of claim 12, further comprising the step of removing excess sugar fatty acid esters.
14. 13. The method of claim 12, further comprising the step of adding polyvinyl alcohol (PvOH), said PvOH and / or sugar fatty acid esters being optionally added separately or in combination as an emulsion.
15. 13. The method of claim 12, wherein the cellulosic material comprises microfibrillated cellulose (MCF), nanofibrillated cellulose or cellulose nanocrystals.
16. The film or paper may be used in any of the following applications: bacon cardboard, insulation, food storage cartons, compost bags, food storage bags, release paper, shipping bags, weed control / barrier fabrics or films, mulching film, flower pots, filler beads, bubble wrap, oil absorbent materials, laminates, envelopes, gift cards, credit cards, gloves, raincoats, OGR paper, shopping bags, diapers, membranes, dishes, tea bags, coffee or tea containers, containers for holding hot or cold beverages, cups, plates, bottles for storing carbonated liquids, bottles for storing non-carbonated liquids.
13. The method of claim 12, wherein the cellulosic material is in the form of a product selected from the group consisting of: lids, films for food packaging, containers for garbage disposals, food handling equipment, fabric fibers, water storage and transport equipment, storage and transport equipment for alcoholic or non-alcoholic beverages, exterior casings or screens for electronic products, interior or exterior parts of furniture, curtains, upholstery materials, fabrics, films, boxes, sheets, trays, pipes, water conduits, clothing, medical devices, pharmaceutical packaging, contraceptives, camping equipment, molded cellulosic materials, and combinations thereof.
17. 13. A product resulting from the process of claim 12 which is biodegradable and / or compostable.
18. 2. The composition of claim 1, wherein the SFAE comprises two or more SFAEs, and at least one SFAE has an HLB value greater than 10.
19. 13. The method of claim 12, wherein the SFAE comprises two or more SFAEs, and at least one SFAE has an HLB value greater than 10.
20. 10. The composition of claim 1, further comprising one or more binders selected from the group consisting of starches, proteins, prolamines, polymers, and PvOH.
21. 13. The method of claim 12, wherein the water resistance imparting formulation further comprises one or more binders selected from the group consisting of starches, proteins, prolamines, polymers, and PvOH.
22. A liquid mixture for obtaining the composition described in claim 1, comprising a cellulosic material and a SFAE, wherein the cellulosic material is a solution containing cellulose fibers or pulp, and the SFAE is present at a concentration of at least 0.025% (wt / wt) of the cellulose fibers or pulp.
Citation Information
Patent Citations
Surface treating agent for papers
JP1976133512A
PAPER PIGMENT, PAPER PRODUCT MANUFACTURING METHOD AND PAPER PRODUCT
JP2008544096A
Coating for paper, paper product, and process for producing paper product
JP2011111703A
Sucrose fatty acid ester-treated powder and cosmetic
JP2011231026A
Coating material for paper, paper product, and method for producing paper product
JP2015232191A